Kinematic characteristics of the stroke and orientation of the hand during front crawl resisted swimming - Gourgoulis, V.; Antoniou, P.; Aggeloussis, N.; Mavridis, G.; Kasimatis, P.; Vezos, N.; Boli, A.; Mavromatis, G. (Journal of Sports Sciences, 2010)
The aim of this study was to examine the acute effect of front crawl sprint resisted swimming with different added resistances on the kinematic characteristics of the stroke and the orientation of the hand. Ten female swimmers swam four maximal trials (25 m) with small, moderate, large, and no added resistance respectively. Four camcorders were used to record the underwater motion of the right hand and digitizing was undertaken using the Ariel Performance Analysis System. Stroke rate, the stroke length, and mean swimming velocity were significantly decreased, whereas the total duration of the stroke and the relative duration of the pull and push phases were significantly increased during resisted swimming. The increase in the total duration of the stroke was accompanied by an increase in absolute pull length, while no alterations were observed in relative pull length or medial-lateral displacements of the hand. Moreover, the mean resultant velocity of the hand, as well as the pitch and the sweepback angles of the hand were not modified. In conclusion, resisted swimming appears to be a specific form of training, at least regarding its acute effect, although long-term effects should be investigated further.